Dwa teksty staropolskie z przełomu XV i XVI wieku. Dekalog i Oracio contra Febrem - Wydra, Wiesław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The article publishes two hitherto unpublished texts which were written at the turn of the 15th century in two incunabula. One is the Polish Decalogue in verse recorded in the incunabulum of the Library of the Canons Regular of the Lateran in Cracow, whereas the second text is the Latin Oracio contra febram with an insertion in the Polish language from the incunabulum of the National Library in Warsaw.